First measurement of the charged current (nu)over-bar(mu) double differential cross section on a water target without( )pions in the final state - Abe,K; Akutsu,R; Ali,A; Alt,C; Andreopoulos,C; Anthony,L; Antonova,M; Aoki,S; Ariga,A; Ashida,Y; Atkin,ET; Awataguchi,Y; et al. (Physical Review D: Particles, Fields, Gravitation and Cosmology, 2020)
This paper reports the first differential measurement of the charged-current ¯νμ interaction cross section on water with no pions in the final state. The unfolded flux-averaged measurement using the T2K off-axis near detector is given in double-differential bins of μ+ momentum and angle. The integrated cross section in a restricted phase space is σ=(1.11±0.18)×10−38  cm2 per water molecule. Comparisons with several nuclear models are also presented.